Journey to senior leadership: Intersectional narratives from women in the leadership pipeline - Vamisile Mbatha; Michele Ruiters (SA Journal of Human Resource Management, 2025)
Orientation: This study explores the factors influencing women’s progression to senior leadership positions, focusing on their experiences within South Africa’s financial services sector.